HUBUNGAN ANTARA PENGENDALIAN DIRI DENGAN PRESTASI BELAJAR SISWA SMKN 1 SUMBAWA BESAR - Hartati, Aluh; Ahmad, Hariadi; Mandasingi, Andika Rifzar (Realita : Jurnal Bimbingan dan Konseling, 2021)
Abstrac: Self-control closely related to person's condition emotional. Individuals who are good at emotions managing themselves control well, because they express emotions properly, appropriately and correctly. Self-control skill individuals have controlling and behavior managing, cognitive, and impulses control achieving individual satisfaction and desires for certain goals, there are aspects of self, behavior, cognitive and satisfaction controlling’s. Learning achievement, the result obtained after carrying out a series of processes learning, which be shown quantitatively by the value or number given the educator to learning subject form of behavior after carrying out the previous learning. The problem examined this research There a Relationship Self-Control with Student Achievement of SMKN 1 Sumbawa Besar? The find out research objective is Relationship Self-Control with Student Achievement of SMKN 1 Sumbawa Besar. The total population is 1222 students and sample of 10% or 127 students. Methods data collection using the questionnaire as main, observation, documentation, interview method’s. Data analysis using the formula product moment. Based on the results of data analysis with a significant level of 5%, the results of the research that rxy value is greater than the r value of the product moment (rxy 0.786> r product moment 0.195) this fact shows rxy value obtained from the results of data analysis can be concluded that: There a Relationship Self-Control with Student Achievement of SMKN 1 Sumbawa Besar. This research it is stated that significant. Keywords: Self-Control, Achievement Learning